Drying Performance, Quality Characteristics, and Financial Evaluation of Indian Mackerel (Rastrilliger Kangurta) Dried by a Solar Tunnel Dryer - Chavan, B. R.; Yakupitiyage, A.; Kumar, S. (Science & Technology Asia, 2015)
Eight drying trials were conducted in each solar tunnel dryer (STD) and compared with open sun drying (OSD). The drying behavior of mackerel drying in STD was studied by comparing eleven different drying models. The Midilli model provided the highest R2 (0.9928), lowest 2χ(0.000406) and RMSE (0.0164). The drying time required for STD and OSD were 27 and 48 h, respectively. The overall drying efficiency of the STD and OSD was about 19.87 and 12%, respectively. STD significantly influenced the biochemical properties such as Free fatty acid (FFA), Peroxide value (PV), Thiobarbituric acid (TBA), total volatile bases nitrogen (TVB-N), Trimethylamine nitrogen (TMA-N) and histamine of dried mackerel. There was a significant positive relationship between drying temperature and time (R2>0.85). No microbial growth on dried product was found in STD dried fish. Sensory quality of dried mackerel was judged by ten experienced sensory panel experts using a seven point hedonic scale. The fish dried at temperatures ranging from 40-46 oC for 20-30 h were awarded the highest scores by the sensory panel. Contour plots of dried mackerel showed that for all sensory attributes examined, panelists preferred fish dried with STD. Time series sensory evaluation of the shelf-life revealed that dried mackerel stored at ambient temperature is acceptable to the sensory panel until 154 and <98 days, for STD and OSD, respectively. The financial analysis showed that the average net income year-1 (for 10 years) is about 45,223 Indian Rupees (INR) and the pay-back period is <1.5 years. Key words: Solar tunnel dryer, dried mackerel, mackerel quality, mackerel drying modeling; open sun drying